Novel Role for Animal Innate Immune Molecules: Enterotoxic Activity of a Snail Egg MACPF-Toxin - Giglio, Matías L.; Ituarte, Santiago; Ibañez, Andrés E.; Dreon, Marcos S.; Prieto, Eduardo; Fernández, Patricia E.; Heras, Horacio (Frontiers in Immunology, 2020)
Gastropod Molluscs rely exclusively on the innate immune system to protect from pathogens, defending their embryos through maternally transferred effectors. In this regard, Pomacea snail eggs, in addition to immune defenses, have evolved the perivitellin-2 or PV2 combining two immune proteins into a neurotoxin: a lectin and a pore-forming protein from the Membrane Attack Complex/Perforin (MACPF) family. This binary structure resembles AB-toxins, a group of toxins otherwise restricted to bacteria and plants. Many of these are enterotoxins, leading us to explore this activity in PV2. Enterotoxins found in bacteria and plants act mainly as pore-forming toxins and toxic lectins, respectively. In animals, although both pore-forming proteins and lectins are ubiquitous, no enterotoxins have been reported. Considering that Pomacea snail eggs ingestion induce morpho-physiological changes in the intestinal mucosa of rodents and is cytotoxic to intestinal cells in culture, we seek for the factor causing these effects and identified PmPV2 from Pomacea maculata eggs. We characterized the enterotoxic activity of PmPV2 through in vitro and in vivo assays. We determined that it withstands the gastrointestinal environment and resisted a wide pH range and enzymatic proteolysis. After binding to Caco-2 cells it promoted changes in surface morphology and an increase in membrane roughness. It was also cytotoxic to both epithelial and immune cells from the digestive system of mammals. It induced enterocyte death by a lytic mechanism and disrupted enterocyte monolayers in a dose-dependent manner. Further, after oral administration to mice PmPV2 attached to enterocytes and induced large dose-dependent morphological changes on their small intestine mucosa, reducing the absorptive surface. Additionally, PmPV2 was detected in the Peyer’s patches where it activated lymphoid follicles and triggered apoptosis. We also provide evidence that the toxin can traverse the intestinal barrier and induce oral adaptive immunity with evidence of circulating antibody response. As a whole, these results indicate that PmPV2 is a true enterotoxin, a role that has never been reported to lectins or perforin in animals. This extends by convergent evolution the presence of plant- and bacteria-like enterotoxins to animals, thus expanding the diversity of functions of MACPF proteins in nature.